Transdisciplinary research before, during and after COVID-19 vaccination in Chile: a virtuoso collaboration with future perspectives - Torres, Juan Pablo; Basso, Leonardo; Saure, Denis; Zuñiga, Marcela; Couve, Andrés; Farfán, Mauricio; de la Maza, Verónica; Campos, Nelson; O’Ryan, Miguel (Frontiers in Public Health, 2024)
The COVID-19 pandemic presented numerous challenges that required immediate attention to mitigate its devastating consequences on a local and global scale. In March 2020, the Chilean government, along with health and science authorities, implemented a strategy aimed at generating relevant evidence to inform effective public health decisions. One of the key strengths of this strategy was the active involvement of the scientific community, employing transdisciplinary approaches to address critical questions and support political decision-making. The strategy promoted collaborations between the government, public and private institutions, and transdisciplinary academic groups throughout each phase of the pandemic. By focusing on pressing problems and questions, this approach formed the foundation of this report which reflects the collaborative effort throughout the pandemic of individuals from the Instituto de Sistemas Complejos de Ingeniería (ISCI), the Faculty of Medicine of the University of Chile, government authorities and industry. Early in the pandemic, it became crucial to gather evidence on how to minimize the impact of infection and disease while awaiting the availability of vaccines. This included studying the dynamics of SARS-CoV-2 infection in children, assessing the impact of quarantines on people’s mobility, implementing strategies for widespread SARS-CoV-2 polymerase chain reaction (PCR) testing, and exploring pool testing for large populations. The urgent need to reduce disease severity and transmission posed a significant challenge, as it was essential to prevent overwhelming healthcare systems. Studies were conducted to predict ICU bed requirements at the local level using mathematical models. Additionally, novel approaches, such as using cellphone mobility-based technology to actively identify infected individuals, and to optimize population sampling, were explored following the first wave of the pandemic. Chile took early action in addressing vaccination through a high-level scientific board, before vaccines became available. Studies conducted during this period included population-based immunologic evaluations of different vaccines, which helped build confidence in the population and supported the need for booster doses and potential vaccination of children. These studies and collaborations, which will be discussed here, have provided valuable insights and will inform future approaches in a post-pandemic world. Importantly, highly conservative estimates indicate that 3,000 lives and more than 300 million USD were saved by this academic-public-private collaborative effort.